PENERAPAN STRATEGI QUESTIONS STUDENTS HAVE (QSH) DALAM PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X1 SMA NEGERI 2 BANGKO KABUPATEN ROKAN HILIR: The Implementation of Questions Students Have (Qsh) Strategies in Direct Learning to Improve Mathematical Learning Outcomes of Class X1 Students of SMA Negeri 2 Bangko Kabupaten Rokan Hilir - Romawati, Romawati (Perspektif Pendidikan dan Keguruan, 2018)
Students' success in learning math is largely determined by the achievement of the learning process and requires the participation of students in writing. This study aims to improve students' mathematics learning outcomes of grade X SMA public 2 Bangko Semester Odd Year 2016/2017 on the subject matter of Equation and Quadratic Inequality by implementing QSH strategy in direct learning. This research includes collaborative classroom action research. Implementation of the research conducted in SMA public 2 Bangko Rokan Hilir Regency in the odd semester of the academic year 2016/2017. The research subjects of class X2 students as many as 26 people. This study consists of two cycles based on Arikunto (2010). Technique of data collection using observation sheet and test result of learning. Data analysis technique with descriptive statistical analysis. Implementation of QSH strategy in direct learning can improve mathematics learning outcomes of students of class X SMA public 2 Bangko academic year 2016/2017, especially on the subject matter of equations and quadratic inequalities.